Isolation and Identification of Bioactive Compounds from Bidens spp. Using HPLC-DAD and GC-MS Analysis and Their Biological Activity as Anticancer Molecules - Kulsoom Zahara; Yamin Bibi; Saadia Masood; Sobia Nisa; Ahmad Sher; Naushad Ali; Sunjeet Kumar; Abdul Qayyum; Waseem Ahmed; Rokayya Sami; Amina A. M. Al-Mushhin; Amani H. Aljahani (Molecules, 2022)
The genus Bidens a member of family Compositae, is widely documented as an ethno-medicinally important genus of plants. In the present study, anticancer potential of three ethno-medicinally important species i.e., B. bipinnata, B. biternata and B. pilosa were tested. For in-vitro evaluation, an MTT (Thiazolyl blue tetrazolium bromide) assay was performed against cervical cancer cells (HeLa), hepatocellular carcinoma (HepG), and adenocarcinoma human alveolar basal epithelial cells (A549). For in vivo evaluation, Artemia salina, Danio rerio, and Caenorhabditis elegans were used. Among all the tested extracts, the ethanol extract of B. biternata appeared to have highest anticancer activity, and the compounds responsible for this activity were identified to be Tris (2,4-di-tert-butylphenyl), 4-hydroxy-2,4′-dimethoxychalcone, and 2,4-di-tert-butylphenol. This is the first report of the isolation of Tris (2,4-di-tert-butylphenyl) phosphate from the genus Bidens and the first report of 4-hydroxy-2,4′-dimethoxychalcone and 2,4-di-tert-butylphenol from B. biternata. Among the isolated compounds, 4-hydroxy-2,4′-dimethoxychalcone showed the highest anticancer activity with an LD50 value of 236.7 µg/mL. Therefore, this compound carries promising potential for being established as a pharmaceutical for chemoprevention and chemotherapy.